2002
DOI: 10.1042/bj20020602
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible inhibition of the bacterial cysteine protease-transpeptidase sortase (SrtA) by substrate-derived affinity labels

Abstract: We report on the first synthesis, kinetic evaluation and application of novel substrate-derived inhibitors against the Staphylococcus aureus cysteine protease-transpeptidase, sortase (staphylococcal surface protein sorting A, SrtA). The peptidyl-diazomethane and peptidyl-chloromethane analogues, Cbz (benzyloxycarbonyl)-Leu-Pro-Ala-Thr-CHN(2) (I) and Cbz-Leu-Pro-Ala-Thr-CH(2)Cl (II) respectively were found to act as time-dependent irreversible inhibitors of recombinant sortase (SrtA(DeltaN)). The peptidyl-chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 27 publications
0
70
0
1
Order By: Relevance
“…Isosteres of the scissile bond, i.e. threonine-glycine for sortase A, achieved inhibition when the LPXT peptides were decorated with either diazoketone or chloromethylketone (13). These peptide-derived inhibitors display favorable K i values, however their rates of inactivation are slow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isosteres of the scissile bond, i.e. threonine-glycine for sortase A, achieved inhibition when the LPXT peptides were decorated with either diazoketone or chloromethylketone (13). These peptide-derived inhibitors display favorable K i values, however their rates of inactivation are slow.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of sortases by small molecules may therefore function as a therapeutic strategy for bacterial infections. Previous work described several sortase inhibitors, including methane-thiosulfonates (12), peptide substrate-derived affinity labels (13), natural compounds (14 -16), vinyl sulfones (17), diarylacrylonitriles (18), bis(indole) alkaloids (19), peptidomimetics (20), isoquinoline alkaloids (16), and threonine analogues (21). However, most of these compounds are either of low activity, lack specificity, or display undesirable structural features that confound therapeutic use.…”
mentioning
confidence: 99%
“…Earlier work used in vitro (inhibition of fluorogenic substrate cleavage) and virtual screening of compound libraries to identify sortase inhibitors (15,(52)(53)(54)(55)(56). Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…In the first of these studies, the threonine-glycine peptide bond was substituted by moieties known to alkylate the active-site thiol of cysteine proteases. These included peptidyl-diazomethane (LPAT-CHN 2 ) and peptidyl-chloromethane (LPAT-CH 2 Cl) (176)…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%